Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Asli Daerah Kota Batam - Syahril Effendi; Baru Harahap (LPPM Universitas Putera Batam, 2020)
The development of information technology is currently growing rapidly, moreover the formation of The purpose of this study is to find answers to determine the effectiveness of parking tax and the contribution of parking tax to local revenue, where in the era of regional autonomy, local governments are required to always increase their regional revenues, such as increasing local tax revenues through billboard tax revenues. Tax revenue through advertising billboards in the city of Batam provides an undeniable contribution to regional revenue. However, in practice it has not yet come close to its true potential, besides that the preparation of this tax target is only based on previous years' experience. The length of this research was conducted from April to July 2016. The object of this research is Batam City Dispenda. The sampling technique used is non-probability sampling, namely the sampling technique using certain considerations or purposive sampling using financial reports from 2015 to 2019. The results of hypothesis testing using the multiple regression analysis method show that simultaneously the effectiveness of parking tax and the contribution of parking tax has a significant effect on local revenue. While partially the effectiveness of parking tax has a significant relationship to local revenue, however, the contribution of parking tax has a significant effect on local revenue at the Batam City Dispenda.